2022
DOI: 10.1098/rsos.221138
|View full text |Cite
|
Sign up to set email alerts
|

Age, empathy, familiarity, domestication and call features enhance human perception of animal emotion expressions

Abstract: Vocalizations constitute an effective way to communicate both emotional arousal (bodily activation) and valence (negative/positive). There is strong evidence suggesting that the convergence of vocal expression of emotional arousal among animal species occurs, hence enabling cross-species perception of arousal, but it is not clear if the same is true for emotional valence. Here, we conducted a large online survey to test the ability of humans to perceive emotions in the contact calls of several wild and domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Whine calls were significantly less likely to be identified in a correct context-whines are wavering, high frequency tonal calls, which may not be perceived as easily as the harsh gakel calls. Greenall et al [26] tested the ability of humans to perceive emotions in the calls of ungulates produced in situations of known emotional arousal and valence and also identified a decrease in correct ratings with age over 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whine calls were significantly less likely to be identified in a correct context-whines are wavering, high frequency tonal calls, which may not be perceived as easily as the harsh gakel calls. Greenall et al [26] tested the ability of humans to perceive emotions in the calls of ungulates produced in situations of known emotional arousal and valence and also identified a decrease in correct ratings with age over 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…
Increases in arousal generally produce vocalizations that are harsher, louder, faster and longer, with a higher frequency ( f0) and a wider frequency range [15].Vocal correlates of valence are less easy to define, though positive contexts mainly elicit shorter call durations [16][17][18]. A growing body of studies has revealed that these acoustic properties appear to accurately predict human ratings of arousal and, to a lesser degree, valence in some animals, including dogs [19][20][21][22][23], pigs [24], silver foxes [25] and wild and domestic ungulates [26].In two studies, the success of participants in correctly classifying and describing emotionality in pig Sus scrofa and dog Canis familiaris calls, respectively, was attributed to use of Morton's motivationstructural rules [20,24]. These rules dictate that a call's frequency [27] is determined by the context it is produced in: high frequency calls are produced in fearful or appeasing contexts, whereas low frequency calls represent aggressive contexts.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, focused on the interpretation of equine acoustic communicative signals (whinnies). Both studies showed that horse-experienced and horse-inexperienced participants were able to identify the valence and arousal of horses' vocalization above chance level [29,30]. Other studies focused on the human ability to identify equine affective states in horses' body language [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vocalizer species, vocal F0 can be influenced by natural selection shaping signal structure, as well as vocalizer sex, body size, and age (Taylor & Reby, 2010), potentially reducing the accuracy of judgments made using the pitch rule. To speculate, this could contribute to the modest (though significantly above-chance) accuracy shown in several studies of heterospecific emotion perception, often 50%–60% on binary forced-choice tasks (Filippi et al, 2017; Greenall et al, 2022; Schwartz & Gouzoules, 2022). These considerations raise the question: how widely do humans apply the pitch rule, and to what extent does use of this heuristic depend on phylogeny and other factors?…”
mentioning
confidence: 99%